Racial Discrimination Experiences Among Black Youth: A Person-Centered Approach. (August 2016) - McNeil Smith, Shardé; Fincham, Frank
This study examines whether subgroups of Black youth exist based on the presence or absence of racial discrimination experiences in the school context and whether these groups varied by gender and household income. Latent transition analyses were performed on racial discrimination indicators derived when youth were in the 8th and 11th grades. Three distinct subgroups of youth emerged. Youth in the Teacher-Peer Perceived Racial Discrimination (PRD) group had a high probability of experiencing racial discrimination from both teachers and peers. Those in the Teacher PRD group had high probabilities of experiencing racial discrimination from teachers and a low probability of experiencing racial discrimination from their peers. Finally, youth in the No PRD group had low probabilities across all racial discrimination indicators. Males were more likely to be in the Teacher-Peer and Teacher PRD groups compared with females. Findings demonstrate the heterogeneity of Black youth's experiences as it relates to race-related stress and several avenues for future research are identified.